Copeptin levels in patients with treatment resistant hypertension before and six months after renal denervation - Bosch, Agnes; Schmid, Axel; Ott, Christian; Kannenkeril, Dennis; Karg, Marina V.; Ditting, Tilmann; Veelken, Roland; Uder, Michael; Schmieder, Roland (American Journal of Hypertension, 2019)
BACKGROUND: Copeptin, the C-terminal peptide of pro-vasopressin, is released from the neurohypophysis and reflects the activity of the hormone arginine vasopressin in patients with hypertension. Elevated copeptin levels are associated with increased cardiovascular and all-cause mortality. The aim of this study is to compare copeptin levels in patients with treatment resistant hypertension (TRH) before and 6 months after renal denervation (RDN). METHODS: Copeptin was measured in 34 patients with TRH and 30 patients with primary hypertension stage 1 or 2 (HT). In addition, copeptin levels were measured in patients with TRH at 6 month follow-up visit after RDN. RDN was performed by an experienced interventionalist applying at least four ablations longitudinally and rotationally within the lengths of each renal artery to cover a full four quadrant ablation. RESULTS: In patients with TRH 24h ambulatory blood pressure (BP) decreased from 154±15/ 87±12 mmHg to 146±13/ 83±7.9 mmHg after RDN (systolic: p=0.001, diastolic: p=0.034). There was no significant change in copeptin levels in these 34 patients with TRH before versus six months after RDN (median 8.4 [interquartile range 3.6-14] vs 8.5 [4.5-13] pmol/l, p=0.334). Patients with TRH had higher copeptin levels (p=0.024) than patients with HT (24h ambulatory BP: 142±11/ 91±8.3 mmHg, copeptin: 4.2 [2.8-6.3] pmol/l). CONCLUSION: Patients with TRH showed 2 fold higher copeptin levels than patients with HT. RDN did not lead to any change of copeptin levels in patients with TRH 6 months after procedure despite significant fall in BP.
EVALuna2:210911